Merit is not for all: a perception of black managers about their proccess of professional rising - Souza, Andrea Alcione; Dias, Rafaela Cyrino Peralva (Organizações & Sociedade, 2018)
Based on a research conducted in Belo Horizonte, with 25 black managers, this article analyzes how the professional rising discourse is based on the idea of personal merit. Considering this central problem and authors such as Pierre Bourdieu, Jessé Souza and Carlos Hasenbalg, the research analyzed the assumptions, functionalities and productive character that the idea of personal merit assumes in the interviewees' discourse. The results obtained point to a perception about the professional rising process with strong meritocratic components, a perception that ignores or minimizes the social, emotional, moral and economic preconditions that interfere in the differential performance obtained by individuals. Moreover, this perception implies a disqualification of any argument that reinforces the racial barriers in their professional rising processes, which contributes to conceal the political, economic and social dimension of racism in the country.